A New Dialogue: Putting People at the Heart of Global Development. Conference Report from the Hunger, Nutrition and Climate Justice Conference: (2013)
With just two years left to achieve the MDGs, and as work begins to shape a new framework for global development post- 2015, the Government of Ireland, as part of Ireland’s EU Presidency, and the Mary Robinson Foundation – Climate Justice, in partnership with the World Food Programme (WFP) and the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS), convened the Hunger- Nutrition – Climate Justice conference in Dublin on 15 and 16 April 2013